PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP PERILAKU GURU DI SDN BANJARBARU KALIMANTAN SELATAN - Karyati, Faridah - (JERAM, 2017)
The purpose of this study is to determine the influence of leadership and communication on work behavior. The research method used is quantitative approach with survey method. Data collection techniques used questionnaires and interviews. Data analysis was done by using descriptive analysis and inferential analysis that is correlation analysis and regression analysis. The sample selected in this study amounted to 120 people from 172 teachers in Banjarbaru Selatan. The result is: (1) leadership has a strong relationship with work behavior, but does not give a direct influence on work behavior (2) communication has a very strong relationship and gives a direct influence on work behavior, (3) there is a positive influence between leadership and communication on the behavior of teachers SDN work in the city of Banjarbaru South Kalimantan. Therefore, it requires transparent and accountable leadership with open communication so as to encourage teachers to work more effectively. Keywords: Leadership, communication, work behavior